Optimal Solution of Fuzzy Assignment Problems Using Ranking Technique (International Journal of Scientific Research in Science and Technology, 2024)
Operation Research has thoroughly studied the Assignment Problem, which is a type of Linear Programming Problem (LPP). It is an important problem in decision-making. In this paper, we are using the Fuzzy technique to simplify Assignment problems and these problems are known as Fuzzy Assignment Problems. In the Fuzzy Assignment Problem, we are using a triangular fuzzy function to optimize the costs. In this paper, we have discussed two formulas: One method is based on an odd number of fuzzy numbers, while the other is based on an even number of fuzzy numbers to find the optimal cost from the given problems by using the Ranking Technique.